CIMAvax-EGF®: Therapeutic Vaccine Against Non-small Cell Lung Cancer in Advanced Stages - Diana Rosa Fernández Ruiz; Olga Lidia Cuevas Pérez (Universidad de las Ciencias Médicas de Cienfuegos, 2017)
Biotechnology is one of the scientific activities deployed by the Cuban State, which shows greater results and impact on the of the Cuban population health. It has increased the therapeutic repertoire in dealing with oncological diseases with products such as CIMAvax-EGF®, the first therapeutic vaccine of its kind, from the Molecular Immunology Center, against non-small cell lung cancer in advanced stages IIIB IV. The application of this product already extends to Primary Health Care with encouraging results, by prolonging the survival of patients with higher quality of life.